Anemia – a scourge to maternal and child development in Bihar, India - Nirala, Santosh Kumar; Rao, Rajath; Naik, Bijaya Nanda; Patil, Shreyas; Verma, Manisha; Singh, CM; Pandey, Sanjay (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Anemia remains a leading contributor to years lived with disability (YLDs), being responsible for 50.3 million (5.82%) YLDs worldwide and 19.3 million (12.03%) YLDs in India, respectively. Results of the National Family Health Survey 2019-2021 (NFHS-5) suggest a high burden of anemia in India among women of reproductive age and children aged 6-59 months at the national level (57%, 67.1%), and in the state of Bihar, India (63.5%, 69.4%). Iron deficiency is the leading cause, accounting for more than half the cases. Anemia bodes harmful implications for both the mother and child, with long-lasting consequences for the latter. Anemia control programs have yielded little benefit despite efforts stretching over five decades. This narrative review aims to highlight the burden of anemia and the probable factors behind it among under-5 children and women of reproductive age in the Indian state of Bihar. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The paper is a narrative review. The following databases were used to search and select literature: PubMed, Web of Science, Scopus, and Google Scholar. In addition, the websites of relevant government departments and national health programs were searched for pertinent material. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. A multitude of reasons seem to be behind the unabated high prevalence in Bihar: low socioeconomic status, gender disparities, traditional customs and practices, food insecurity, lack of diverse diets, poor consumption, and no adherence to iron and folic acid (IFA) supplements, groundwater contamination with arsenic and fluoride, and supply chain mismanagement, all playing roles of varying degree. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. An all-encompassing approach and not merely the provision of IFA supplements are necessary to unravel the intricate web of factors that lead to anemia.